Seleção de espécies e procedências de Pinus sp para a região de Assis, Estado de São Paulo - Souza, Francine Beatriz de [UNESP] (2015)
In forest breeding programs the selection of species and provenances of the best species are the two most important steps because in these steps the largest genetic gains are capitalized . This is done by using species and provenance test established in the sites of interest and evaluating growth and survival traits. This work aimed the selection of species and provenances of Pinus species for the region of Assis, state of São Paulo. The test was installed in Assis State Forest, in the western region of São Paulo. The experimental design was a randomized complete block design with three treatments represented species (Pinus oocarpa, P. maximinoi and P; tecunumanii) and two to three provenances, represented the provenances within species, four replications (blocks) and square plots with 49 plants (7 x 7), in a spacing of 3 x 2.5 m. After 21 years of planting, were measured the diameter at breast height (DBH), total height (ALT), individual real volume (VOL) and the survival rate (SOB) in the trial. Significant differences among species were detected only for SOB, indicating the possibility of selection among species. The genetic divergence between species varied between zero to 0.4326, which indicates that most of genetic variability for the traits is distributed within species and that the genetic differences between species for ALT, VOL and SOBRE are more salient than the difference between the provenances studied. Although no significant differences comparing the average of traits among species, P. oocarpa showed the highest values for ALT; VOL and SOB and P. maximinoi the highest growth in DBH. Significant positive correlations were observed between the DAPxALT (0,403; p<0,05), DAPxVOL (0,792; p<0,01), ALTxVOL (0,874; p<0,01). Thus, there is the possibility to select individuals of three species based on phenotypic observations in a trait and indirectly change the average phenotypic of other ...